A New Series of Strigolactone Analogs Derived From Cinnamic Acids as Germination Inducers for Root Parasitic Plants - Suzuki, Taiki; Kuruma, Michio; Seto, Yoshiya (Frontiers in Plant Science, 2022)
Root parasitic plants such as Striga and Orobanche cause significant damage on crop production, particularly in sub-Saharan Africa. Their seeds germinate by sensing host root-derived signaling molecules called strigolactones (SLs). SL mimics can be used as suicidal germination inducers for root parasitic plants. Previous attempts to develop such chemicals have revealed that the methylbutenolide ring (D-ring), a common substructure in all the naturally occurring SLs, is critical for SL agonistic activity, suggesting that it should be possible to generate new SL mimics simply by coupling a D-ring with another molecule. Because structural information regarding SLs and their receptor interaction is still limited, such an approach might be an effective strategy to develop new potent SL agonists. Here, we report development of a series of new SL analogs derived from cinnamic acid (CA), the basis of a class of phenylpropanoid natural products that occur widely in plants. CA has an aromatic ring and a double-bond side-chain structure, which are advantageous for preparing structurally diverse derivatives. We prepared SL analogs from cis and trans configuration CA, and found that all the cis-CA-derived SL analogs had stronger activities as seed germination inducers for the root parasitic plants, Orobanche minor and Striga hermonthica, compared with the corresponding trans-CA-derived analogs. Moreover, introduction of a substitution at the C-4 position increased the germination-stimulating activity. We also found that the SL analogs derived from cis-CA were able to interact directly with SL receptor proteins more effectively than the analogs derived from trans-CA. The cis isomer of CA was previously reported to have a growth promoting effect on non-parasitic plants such as Arabidopsis. We found that SL analogs derived from cis-CA also showed growth promoting activity toward Arabidopsis, suggesting that these new SL agonists might be useful not only as suicidal germination inducers for root parasitic weeds, but also as plant growth promoters for the host plants.